Redistricting dan Polarisasi Partai di Dewan Perwakilan Rakyat Amerika Serikat - Mariana, Mariana (Lembaga Yasin AlSys, 2022)
The increasing level of party polarization observed in contemporary Congress has been attributed to a variety of factors. One of the more commonly recurring themes among congressional political observers is that the changes in district boundaries resulting from the redistricting process are the root cause. Using a new data set connecting congressional districts from 1962 to 2002, we offer hands-on testing of these claims. Our results show that despite an overall trend of increased polarization, districts that have undergone significant changes as a result of redistricting are becoming more polarized. Although the effect is relatively simple, it suggests that redistricting is one among other factors that generates party polarization in the House and may help explain the increasing level of polarization in the House relative to the Senate.